The emergence of Lyme disease and other tick-borne diseases - Fish, Durland (Henry Stewart Talks, 2011)
Expansion of the vector tick population North America due to environmental change, Mutual expansion of the spirochetal agent of Lyme disease alongside tick expansion, Agents of other human diseases are following, Babesiosis, Anaplasmosis, Flaviviral encephalitis, Other diseases